Representações do corpo deficiente no cinema: uma análise dos filmes ‘Feliz Ano Velho’ e ‘Intouchables’ - SOBRAL, Maria Lizete Sampaio (Universidade Federal do Pará, 2023)
The view built on the representations of physical disability in humanbeingshas been, throughout history, often associated with the notion of stigma, whichnormallyrelates the disabled body to someone incapable, discriminated against, possessinga sufferingcondition. As a proposal of this research , we present other approaches to this relationship,which do not dwell solely on conventional notions, but which, on the contrary, cancoverabroader and, at the same time, deeper field of investigation and debate, when confrontingmain themes such as 'body', 'disability, 'cinema', interrelated by the idea of socialrepresentations. We prioritize analyzing the disabled body when this body takes acentralplace in the cinematographic narrative. For this, this study is based on the analysis of twofilms that present similar narratives and content. The films are 'FELIZ ANOVELHO', inBrazilian cinema, and 'INTOUCHABLES', in French cinema. Both are inspiredbyliteraryproductions, more precisely by autobiographies. Its central characters, Mário, in the Brazilianfilm 'FELIZ ANO VELHO', Philippe in 'INTOUCHABLES', a French film, live similar lifeexperiences, as both suffer real situations of accidents: Mário diving into a lake andhittinghishead, Philippe when falling from a paraglider, accidents that leave themforeverinwheelchairs. The option for the analysis developed here is due to considering the possibilityof confronting symmetries, or not, between the films, that is, by the similaritiesanddifferences existing in the stories lived by their protagonists. With an emphasis ontherelationships we seek to understand, we opted for a more specific study on the disabledbodyin cinema as the basis for building the research. Thus, the process experiencedbytheprotagonists of the films and the way in which the issue of the disabled body is addressedineach film, become central themes of this debate. The research has its theoretical basisinthetheories and dialogue of the Social Sciences, regarding the idea of social representation, withArt and Cinema, as well as brings reflections from scholars such as Maria Lúcia Homem,Lacan and Freud, regarding , mainly, his particular elaboration on the notions of real body,symbolic body and imaginary body